Experiences with the Design, Fielding, and Evaluation of a Real-Time Communications Agent - Horvitz, Eric; Sarin, Raman; Koch, Paul; Rui, Yong (2003)
We review the design and evaluation of a fielded communications agent that routes telephone calls for several hundred people at our organization. In an advanced mode of operation, the system performs a cost-benefit analysis to balance the priority of calls with the context-sensitive cost of interrupting users. We discuss the challenges with developing a communications agent spanning client-side software and telephony infrastructure. We focus on metaphors and tools that allow users to specify priorities and costs of interruption. We report on the results analysis of surveys and monitored logs of preferences and activities.